HIEDQUAL (High Education Quality) Dan Kepuasan Mahasiswa: Peran Reputasi Universitas Sebagai Variabel Mediasi - Rully Arlan Tjahyadi; Cen Lu; Jeslyn Fionita (Forum Manajemen Indonesia (FMI), 2018)
Customers are the main part for the success of any business. Measurement of customer satisfaction is becoming vital for the long term sustainability of any organization especially service organization. In higher education context, student is a primary customer. So student satisfaction is important concept in facing increased pressure of the competition in the education service industry. It is vital for high education institution to have a proper understanding what determinants of student satisfaction. The most of customer satisfaction study have focused on service quality as an antecedent of student satisfaction. Model of service quality that will be examined in this study is HiEDQUAL model of service quality. Five aspects in measuring service quality are teaching and course content, administrative service, academic facilities, university facilities, and service support. This study will also test the role of university reputation as a moderator variable. Samples of this study are active students of Faculty of Economics of Maranatha Christian University. Questionnaires will distribute for 350 students. Research hypothesis will be tested with regression analysis for moderating variable. Keywords: Service Quality, High Education Quality, Reputation, Customer Satisfaction